(untitled) (Avocetta, 2016)
Sex ratio is a parameter worth to be monitored in small animal populations, as it has wide implications for their conservation. Morphological sex identification in birds, especially in the Accipitridae, can be difficult if the animals are young or when there is no appreciable sexual dimorphism. Sex determination can be impossible when few and/or degraded biological material (e.g. feathers, blood traces, decomposed carcasses) is available. In this case, molecular markers represent the analytical method of choice. Two molecular Amplification Refractory Mutation System (ARMS) protocols, both based on the amplification of portions of the Chromo-Helicase DNA-binding protein (CHD1) gene, were tested on tissues from 6 Griffon vultures Gyps fulvus of known sex, and subsequently, on 9 shed feathers (i.e. degraded samples from individuals of unknown sex) collected on feeding sites. Protocol 1 consisted of one PCR reaction yielding two amplicons with larger sizes than those produced with Protocol 2, which, in contrast, consisted of two PCRs. Our results show that, overall, both molecular protocols are suitable for sex identification in the Griffon vulture. In particular, when good quality/quantity DNA is available (e.g. DNA from feathers of live animals, fresh or frozen blood and tissues), Protocol 1 was faster than Protocol 2, since one single PCR is performed. On the other hand, Protocol 2 can better suite to poor or degraded DNA (e.g. extracted from shed feathers or decomposed tissues), because the two amplifications produce smaller fragments. We selected Protocol 1 to analyse good quality DNA from feathers of 89 free-ranging Griffons, sampled during capture and ringing activities (years 2013-2015) by the Forest Service within the Monte Velino Reserve (central Apennines, Italy). The sex ratio obtained for this reintroduced population was 1: 2.07 (29 females and 60 males). We also explored the potential of applying this method in other 10 bird species: molecular and morphological identification of sex always yielded concordant results. This study shows that Protocol 1 can be used for sex identification in Griffons and other mainly monomorphic species for which population studies or monitoring programs are planned, or when sex could not be determined from few remains of otherwise dimorphic species.